Development strategies for West Africa - Ehui, Simeon K.; Benin, Samuel; Spencer, D.S.C. (International Food Policy Research Institute, 2000)
This brief considers the comparative advantage of strategies for West Africa based on the four agroecological zones - humid, subhumid, semiarid, and arid - found there. These zones are defined by the amount and distribution of rainfall, temperature, and length of the annual growing period.